Effects of microstructure on the mechanical properties of Ti2AlC in compression. (15th January 2018) - Benitez, Rogelio; Gao, Huili; O'Neal, Morgan; Lovelace, Peter; Proust, Gwénaëlle; Radovic, Miladin
Abstract: This study investigates the effect of microstructure, specifically the grain size and TiAlx impurity, on the compressive strength and hysteretic behavior of Ti2 AlC at room temperature. Given the plate-like nature of the MAX phase grains, the length and thicknesses of over 100 grains for each microstructure were measured. A Hall-Petch like relationship between compressive strength and the grain length was observed, but not such a relationship was observed with the grain thickness. Results from cyclic compression testing in combination with resonant ultrasound spectroscopy show that room temperature mechanical response of Ti2 AlC can be divided into four stress regions regardless of the variation in grain size and/or amount of impurities. The grain size effect on the transition stresses for stress regions was also investigated. It was found that all transition stresses, between the different stress regions, also follow different Hall-Petch-type relationships. Graphical abstract: Image 1